Social innovation and sustainable technologies in social interorganizational relationships: an experimental study in CREDITAG-RO - de Oliveira, Nilza Duarte Aleixo; Silva, Tania Nunes da (Revista de Administração da UFSM, 2012)
http://dx.doi.org/10.5902/198346595655 This paper derived from the thesis project defended by the Federal University of Rio Grande do Sul, aimed to propose a framework that allows the observation of the presence of social innovation, social technologies and collective entrepreneurship in interorganizational relationships. The cooperatives chosen to analyze the relationship of Inter-cooperation are the cooperatives of the Rural System of Credit Cooperatives of Family Farming and Economic Solidarity - CREDITAG in Rondônia. The study was set up as an experiment, with primary data collected through 11 in-depth interviews, to identify the social technologies developed, motivation for collective entrepreneurship, awakening new interest in cooperative skills and projecting itself as an important process of social innovation.